Native mass spectrometry goes more native: investigation of membrane protein complexes directly from SMALPs. Issue 97 (19th November 2018) - Hellwig, Nils; Peetz, Oliver; Ahdash, Zainab; Tascón, Igor; Booth, Paula J.; Mikusevic, Vedrana; Diskowski, Marina; Politis, Argyris; Hellmich, Yvonne; Hänelt, Inga; Reading, Eamonn; Morgner, Nina
Abstract : Other than more widely used methods, the use of styrene maleic acid copolymers allows the direct extraction of membrane proteins from the lipid bilayer into SMALPs keeping it in its native lipid surrounding. Abstract : Other than more widely used methods, the use of styrene maleic acid allows the direct extraction of membrane proteins from the lipid bilayer into SMALPs keeping it in its native lipid surrounding. Here we present the combined use of SMALPs and LILBID-MS, allowing determination of oligomeric states of membrane proteins of different functionality directly from the native nanodiscs.